ANALISIS PENGGUNAAN FITUR AIR MAX PADA PERANGKAT UBIQUITY UNTUK PENINGKATAN THROUGHPUT - ., Tuah Kurniawan (Jurnal Teknik Elektro Universitas Tanjungpura, 2017)
ABSTRACT- Right now Internet use has become one of the needs of people from various backgrounds, ranging from companies, offices, universities, schools, households and others. PT. Jawa Pos National Network Medialink is a company engaged in technology-based services to the public Internet network in Pontianak City in general. The aim of this thesis was to analyze the quality of the Internet network service client PT. JPNN Medialink Pontianak using Throughput parameters and to determine any factors that can affect the quality of the Internet network services, so PT. JPNN Medialink Pontianak can improve the performance of their service that meets the standards of Quality of Service (QoS). In this study, prepared 1 computer as a media testers to see how the quality of service from the network to be researched in the client. Where in the computer is connected directly to the internet and is at an ISP and already terisntal Google earth application. The research was done in 5 client in PT. JPNN Medialink Pontianak in which the test was performed twice on each client, before and after using the Air Max features with the aim to obtain some comparative research data. The average yield Throughput testing parameters for 5 client amounted to 50.01% with the index 2 medium category, the average index for the standard TIPHON all QoS parameter is 2.7 with category less than satisfactory and average internet access speed is 64050, 0496 bps medium category. Keywords: Throughput, Air Max, Ubiquity, AirOS, QoS, Internet Access Speed.